KEDUDUKAN MAZHAB, TAKLID DAN IJTIHAD DALAM ISLAM - Karimuddin, Muhammad Zuhdi (IAIN LANGSA, 2019)
The Mazhab is interpreted as a way of thinking of a mujtahid in finding law from the original source, namely the Qur'an and Hadith, or the opinion of a mujtahid. The mazhab means tofollow the opinion of Islamic jurists. The mazhab can also be interpreted as submitting to theImam of the mazhab or religious followers of the mazhab of law. The mazhab or follow themazhab as an alternative for those who are clouds or people who are unable to do ijtihad.